Prebiotic Effect of Fructooligosaccharide in the Simulator of the Human Intestinal Microbial Ecosystem (SHIME (R) Model) - Sivieri, Katia [UNESP]; Morales, Martha L. Villarreal; Saad, Susana M. I.; Adorno, Maria A. Tallarico; Sakamoto, Isabel Kimiko; Rossi, Elizeu Antonio [UNESP] (Mary Ann Liebert, Inc, 2014)
Maintaining "gut health'' is a goal for scientists throughout the world. Therefore, microbiota management models for testing probiotics, prebiotics, and synbiotics have been developed. The SHIME (R) model was used to study the effect of fructooligosaccharide (FOS) on the fermentation pattern of the colon microbiota. Initially, an inoculum prepared from human feces was introduced into the reactor vessels and stabilized over 2 weeks using a culture medium. This stabilization period was followed by a 2-week control period during which the microbiota was monitored. The microbiota was then subjected to a 4-week treatment period by adding 5 g/day-1 FOS to vessel one (the "stomach'' compartment). Plate counts, Denaturing Gradient Gel Electrophoresis (DGGE), short-chain fatty acid (SCFA), and ammonium analyses were used to observe the influence of FOS treatment in simulated colon compartments. A significant increase (P < .01) in the Lactobacillus spp. and Bifidobacterium spp. populations was observed during the treatment period. The DGGE obtained showed the overall microbial community was changed in the ascending colon compartment of the SHIME reactor. FOS induced increase of the SCFA concentration (P < .05) during the treatment period, mainly due to significant increased levels of acetic and butyric acids. However, ammonium concentrations increased during the same period (P < .01). This study indicates the usefulness of in vitro methods that simulate the colon region as part of research towards the improvement of human health.
Keywords: FOS; gastrointestinal resource management; gut microbiota; in vitro evaluation